The Influence of English as Medium of Instruction (EMI) on the First and Second Language Acquisition of Bilingual School Students: A Case Study - Pujiani, Tri; Sukmawati, Ida Dian; Adzkiyah, Maulina (Universitas Nahdatul Ulama Surabaya, 2023)
English as a Medium of Instruction (EMI) is a term used for learning activities where English is used as the main language. This approach is widely adopted by bilingual schools as it allows learners to learn both their first and second language at the same time. While EMI has many advantages, the impact of this method on children's first and second language acquisition remains largely unknown. Therefore, through a case study, this research aims to examine the effect of EMI on children's first and second language acquisition in bilingual schools. This research will be conducted in a school that applies EMI in the Purwokerto area, namely Tiga Bahasa Putera Harapan School, with a sample of grade 3 students and teachers as respondents. This sample is randomly selected using a convenience sampling technique. Data for this study will be obtained through observations, speaking tests in Indonesian and English, and interviews. The results of this study show that there is no significant difference between the average English score (85.47) and Indonesian score (84.76) of students taught using EMI. Despite its status as an international standard school, national values and love for the country are still instilled through various curricular and co-curricular activities. This shows that with proper management, EMI does not affect the first and second language acquisition of children attending bilingual schools. To improve children's English proficiency, English needs to be introduced early through environmental conditioning that supports the use of English in daily life.